2019
DOI: 10.1002/ecs2.2728
|View full text |Cite
|
Sign up to set email alerts
|

Trade‐offs and synergies in a payment‐for‐ecosystem services program on ranchlands in the Everglades headwaters

Abstract: Increasingly, agriculture is recognized as valuable not only for food production, but also for regulating and supporting ecosystem services such as those encompassing biodiversity and water. Various government programs provide incentives to farmers and ranchers to maintain ecosystem services, with an emerging focus on payment‐for‐ecosystem services (PES) programs. However, interactions among ecosystem services, including synergies or trade‐offs, at spatial scales relevant to land managers are not well understo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 67 publications
0
4
0
1
Order By: Relevance
“…For example, in the Midwestern United States, Werling et al ( 2014) reported significantly higher plant and predatory arthropod richness in native prairies compared to adjacent cultivated monoculture. Boughton et al (2019) showed that more intensely managed ranches had a greater potential for ecosystem disservices in the context of wetland restoration projects such as increased cover of non-native plants, abundant mosquitoes, and lower amphibian abundance. Furthermore, native perennial grasslands preserve plant genetic diversity by harboring unique seed banks (Minns et al 2001), and species genetic diversity is key for adaptation to adverse environments and increased resistance to pests and diseases (Zhang et al 2007).…”
Section: Biodiversity and Habitatmentioning
confidence: 99%
“…For example, in the Midwestern United States, Werling et al ( 2014) reported significantly higher plant and predatory arthropod richness in native prairies compared to adjacent cultivated monoculture. Boughton et al (2019) showed that more intensely managed ranches had a greater potential for ecosystem disservices in the context of wetland restoration projects such as increased cover of non-native plants, abundant mosquitoes, and lower amphibian abundance. Furthermore, native perennial grasslands preserve plant genetic diversity by harboring unique seed banks (Minns et al 2001), and species genetic diversity is key for adaptation to adverse environments and increased resistance to pests and diseases (Zhang et al 2007).…”
Section: Biodiversity and Habitatmentioning
confidence: 99%
“…(Bohlen et al, 2009; Bohlen & Villapando, 2011; Boughton et al, 2019; Capece et al, 2007; Chamberlain et al, 2017; Gomez‐Casanovas et al, 2020; Jansen et al, 2019; Silveira et al, 2011; Sonnier et al, 2018; Zielinski et al, 2006)…”
Section: Overviewunclassified
“…For example, some grassland management such as patch-burn grazing can improve nutrient-use efficiency and forage quality 66 , 71 , which may reduce reliance on costly fertilizer inputs and ameliorate nutrient loads flowing to embedded wetlands. Payment for ecosystem services could also shift incentives toward hydrological and nutrient retention in the connected wetlands, and foster best management practices (e.g., buffer strips) to offset regional effects of grassland intensification 72 .…”
Section: Discussionmentioning
confidence: 99%